Двоемирие как художественное предчувствие истории: фильм Ю. Ильенко и С. Параджанова «Лебединое озеро. Зона» (1990) - Nikoriak, Nataliia (TSU Shota Rustaveli Institute of Georgian Literature, 2019)
The historical events of the late 80-s and early 90-s of the XX century have provoked the emergence of a few masterpieces that have simultaneously become both a “verdict” and a “prophecy” for the existing system. A good example of this phenomenon is the film by Yuriy Illienko “Swan Lake. The Zone”, produced on the basis of “oral narrations” and short stories by Sergey Parajanova bout the years he spent in imprisonment. This movie may be regarded as a forerunner of the Communist regime collapse.
The Duality of the World as an Artistic Premonition of History: the Film by Y. Illienko and S. Parajanov „Swan Lake. The Zone“ (1990)
Keywords: Yuriy Illienko, Sergey Parajanov, “Swan Lake. The Zone”, Duality